Derivation of original RESP atomic partial charges for MD simulations of the LDAO surfactant with AMBER: applications to a model of micelle and a fragment of the lipid kinase PI4KA. Issue 1 (2nd January 2017) - Karakas, Esra; Taveneau, Cyntia; Bressanelli, Stéphane; Marchi, Massimo; Robert, Bruno; Abel, Stéphane
Abstract : In this paper, we describe the derivation and the validation of original RESP atomic partial charges for the N, N-dimethyl-dodecylamine oxide (LDAO) surfactant. These charges, designed to be fully compatible with all the AMBER force fields, are at first tested against molecular dynamics simulations of pure LDAO micelles and with a fragment of the lipid kinase PIK4A (DI) modeled with the QUARK molecular modeling server. To model the micelle, we used two distinct AMBER force fields (i.e. Amber99SB and Lipid14) and a variety of starting conditions. We find that the micelle structural properties (such as the shape, size, the LDAO headgroup hydration, and alkyl chain conformation) slightly depend on the force field but not on the starting conditions and more importantly are in good agreement with experiments and previous simulations. We also show that the Lipid14 force field should be used instead of the Amber99SB one to better reproduce the C(sp3)C(sp3)C(sp3)C(sp3) conformation in the surfactant alkyl chain. Concerning the simulations with LDAO-DI protein, we carried out different runs at two NaCl concentrations (i.e. 0 and 300 mM) to mimic, in the latter case, the experimental conditions. We notice a small dependence of the simulation results with the LDAO parameters and the salt concentration. However, we find that in the simulations, three out of four tryptophans of the DI protein are not accessible to water in agreement with our fluorescence spectroscopy experiments reported in the paper. Graphical abstract: